Is the maximal lactate steady state concept really relevant to predict endurance performance? - Niemeyer, M.; Gündisch, M.; Steinecke, G.; Knaier, R.; Beneke, R. (European Journal of Applied Physiology, 2022)
Purpose There is no convincing evidence for the idea that a high power output at the maximal lactate steady state (PO_MLSS) and a high fraction of VO2max at MLSS (%VO2_MLSS) are decisive for endurance performance. We tested the hypotheses that (1) %VO2_MLSS is positively correlated with the ability to sustain a high fraction of VO2max for a given competition duration (%VO2_TT); (2) %VO2_MLSS improves the prediction of the average power output of a time trial (PO_TT) in addition to VO2max and gross efficiency (GE); (3) PO_MLSS improves the prediction of PO_TT in addition to VO2max and GE.